The Possible Existence of Parallel Universes Within the Total Number of Hypercubic Lattices of a Multidirectional Discrete Space - Groot, Christiaan T. (European Journal of Applied Sciences, 2023)
The very many subspaces of a multidirectional hypercubic lattice provide a space structure not present in conventional space demonstrating the possibility of superstructures of self-contained universes of nuniverse subspaces. To show that, first the total number of subspaces nsubspaces of the expanded lattice is determined from the discrete gravitational constant, that is, expressed in the units of a lattice. The total number of subspaces nsubspaces is so large that further structuring in universes of lattices is possible. Starting from the plausible assumption that interactions are limited to one subspace, it is argued that only particles present in one of the universes will interact. Since nsubspaces/nuniverse >1, different autonomous universes are possible.